Analisis Pelayanan pada Kepuasan Pelanggan Rawat Inap Rumah Sakit - Daniel Wisuda Purba; Sisca Septiani; Hendro Budiyanto (Departement of Mathematics Education, 2023)
The objectives of the study were: 1) to find out the characteristics of RSPMK inpatient customers; 2) to find out how much the level of customer satisfaction of RSPMK inpatients in West Jakarta. This research was conducted with a survey using a sample of RSPMK patients, the sample was taken from all RSPMK inpatients as many as 63 respondents. The results of data processing and data analysis can be concluded that the results of data processing and data analysis of the level of RSPMK inpatient customer satisfaction both in the dimensions of tangibles, reliability, responsiveness, assurances, and empathy from RSPMK both in closed questions and open questions distributed through questionnaires can be concluded that the level of RSPMK customer satisfaction is good. Nevertheless, some positive and negative comments were also found from respondents. Positive comments regarding the level of customer satisfaction of RSPMK include that the rooms are comfortable, the food menu is decent, the building is good, and has private hospital standards so that it continues to be maintained, especially in the company's guarantee, the service is very fast, including confirmation to insurance companies, the service is good enough, especially the doctor is good, especially the anesthesiologist, friendly and polite, also the nurses are good, maintain the quality of the rooms, and the important thing is that the rates are cheap. While negative comments regarding RSPMK customer satisfaction include the facilities, please pay more attention, especially the bathroom, the service is less friendly, especially administrative services, more attention to the registration section, the nurse is very slow at work and lacks empathy, patient handling is long, noisy because night visitors are still in the room, the doctor's service is not clear visiting hours, and most of them come in the afternoon, the tariff is a bit expensive, there are some flies that disturb in the treatment room, visiting or visiting hours are not clear.